Agnotologia pedagogiczna. Zarys problematyki. Trzy subiektywne opowieści - Kwieciński, Zbigniew (Studia Edukacyjne, 2020)
The term „agnotology” was introduced by Robert Proctor. Agnotology is the study on the spread of ignorance, its social scope and impact, causes and effects. The author tried to analyze whether it is possible that ignorance is disseminated by schools, the principal institution of the Enlightenment, i.e. not only of equipping invididuals with broad knowledge, but of taking care of each individual’s ability to judge (critical thinking). The author discusses three examples of deliberate structural changes to indicate that school „reforms” may bring about effects opposite to the intended ones, have an offside effect of belated imitation and widespread side effects, which destroy the entire education system.